Multilocus phylogeny of Bornean Bent-Toed geckos (Gekkonidae: Cyrtodactylus) reveals hidden diversity, taxonomic disarray, and novel biogeographic patterns - Davis, Hayden R.; Chan, Kin Onn; Das, Indraneil; Brennan, Ian G.; Karin, Benjamin R.; Jackman, Todd R.; Brown, Rafe M.; Iskandar, Djoko T.; Nashriq, Izneil; Grismer, L. Lee; Bauer, Aaron M. (Elsevier, 2020)
The gekkonid genus Cyrtodactylus is a highly diverse group of lizards (280+ species), which covers an expansive geographic range. Although this genus has been the focus of many taxonomic and molecular systematic studies, species on the Southeast Asian island of Borneo have remained understudied, leading to an unclear evolutionary history with cascading eﬀects on taxonomy and biogeographic inferences. We assembled the most comprehensive multilocus Bornean dataset (one mitochondrial and three nuclear loci) that included 129 novel sequences and representatives from each known Cyrtodactylus species on the island to validate taxonomic status, assess species diversity, and elucidate biogeographic patterns. Our results uncovered a high proportion of cryptic diversity and revealed numerous taxonomic complications, especially within the C. consobrinus, C. malayanus, and C. pubisulcus groups. Comparisons of pairwise genetic distances and a preliminary species delimitation analysis using the Automatic Barcode Gap Discovery (ABGD) method demonstrated that some wide-ranging species on Borneo likely comprise multiple distinct and deeply divergent lineages, each with more restricted distributional ranges. We also tested the prevailing biogeographic hypothesis of a single invasion from Borneo into the Philippines. Our analyses revealed that Philippine taxa were not monophyletic, but were likely derived from multiple separate invasions into the geopolitical areas comprising the Philippines. Although our investigation of Bornean Cyrtodactylus is the most comprehensive to-date, it highlights the need for expanded taxonomic sampling and suggests that our knowledge of the evolutionary history, systematics, and biogeography of Bornean Cyrtodactylus is far from complete.